Legislative Stabilization Condition and its role in Oil Contracts Arbitration (Al-MAHAD Journal, 2023)
Oil contracts are the key contracts that raised broad controversy in the legal, juristic and economic spheres, respectively, and this controversy comes from several sides, primarily the matter of those contracts, which is petroleum, which is an economic commodity that was economically discovered from the end of 19th century to date.Importance of this commodity drove diversity and multiplicity of the conditions contained in those contracts. The key and most controversial condition is that of legislative stabilization which was widely debated and discussed in juristic media of all approaches. We have discussed the condition in the research titled "condition of legislative stabilization and its role in oil contracts arbitration" in three sections. The first section concerns definition of legislative stabilization condition and types in two topics. The first topic defines the legislative stabilization condition and the second for definition of its types. In the second section, we handled the stance of jurisprudence and the consequences thereof in three topics the first of which is that of the stance of jurisprudence and the second in its legal framing and consequences. In the third section, we handled the role of legislative stabilization condition in the terms of oil contracts arbitration and handled the key arbitral awards in the contracts the matter of investigation which contained condition of legislative stabilization in four topics the first of which is Texaco Arbitral Award of 1977, the second is Liamco Arbitral Award of 1977, the third is Agip Arbitral Award of 1979, and the fourth and last one is Aminoil Arbitral Award. We concluded by investigation set of conclusions and recommendations that we noted in place.